Prioritizing Healthcare Delivery in a Conflict Zone; Comment on "TB/HIV Co-Infection Care in Conflict-Affected Settings: A Mapping of Health Facilities in the Goma Area, Democratic Republic of Congo" - Robin Wood; Eugene T Richardson (Kerman University of Medical Sciences, 2013)
Nowhere are the barriers to a functional health infrastructure more clearly on display than in the Goma region of Democratic Republic of Congo. Kaboru et al. report poorly integrated services for HIV and TB in this war-torn region. Priorities in conflict zones include provision of security, shelter, food, clean water and prevention of sexual violence. In Goma, immediate health priorities include emergency treatment of cholera, malaria, respiratory illnesses, provision of maternal care, millions of measles vaccinations, and management of an ongoing rabies epidemic. It is a daunting task to determine an essential package of medical services in a setting where there are so many competing priorities, where opportunity costs are limited and epidemiologic information is scarce. Non-governmental agencies sometimes add to the challenge via an insidious reduction of state sovereignty and the creation of new levels of income inequality. Kaboru et al. have successfully highlighted many of the complexities of rebuilding and prioritizing healthcare in a conflict zone.